Effects of Population Density on Survival, Development Time, Fecundity and Hatchability of Samia cynthia ricini Boisduval - Nurkomar, Ihsan; Trisnawati, Dina Wahyu; Wening, Firda Kartika (Indian Journal of Entomology, 2023)
Samia cynthia ricini Boisduval Lepidoptera:Saturniidae is a lepidopteran insect that has a gregarious behaviour during their larval stage. This research aimed to determine the minimum population limit of larvae that can support the survival of S. c. ricini by observing the development time, fecundity, and hatchability of eggs produced by adult moths under different larval densities rearing conditions. The research was conducted by observing the lifecycle and development of S. c. ricini at different population densities. The results showed that density had effect on the development time of S. c. ricini egg only. Population density also affects the survival and adult fecundity of S. c. ricini. A density of 30 is the minimum population required to support the success of S. c. ricini’slife. Samia cynthia ricini reared at this density had the highest survival rate, faster egg development time, heavier cocoon shell weight and highest fecundity.